A corpus analysis of metadiscourse in good and weak undergraduate academic writing / Amaal Fadhlini Mohamed - Mohamed, Amaal Fadhlini (2014)
The concept of metadiscourse is one of the essential areas in academic writing. However, little is known as to how it is actually used by undergraduates in their writing. In academic writing, metadiscourse refers to the linguistic expressions or terms used in a piece of writing to organize the ideas and contents of a text while leading the readersto understanding. This research identifies categories and forms of metadiscourse used in a corpus of undergraduate academic writing in Asasi Science and Engineering (MUAWRISE corpus). A comparison of metadiscourse used between two sub-corpora of good (GAW corpus) and weak (WAW corpus) academic writing was done. This present study is therefore relevant as it investigates how metadiscourse markers are applied by tertiary level students to write effectively in their academic writing. Since metadiscourse has never been directly taught as a subject to undergraduate students, it may contribute to raising their awareness on metadiscourse functions in effective writing. This is a corpus-based research study that involves qualitative (conceptual analysis) and quantitative (descriptive analysis) approaches to identify metadiscourse items in the coipus. Although this corpus comprises of both good essays (GAW corpus) and weak essays (WAW corpus), however, they show a higher frequency of use in interactive metadiscourse as compared to interactional metadiscourse category. It is found that more metadiscourse items (based on Occurrence per 10, 000 words) were found in weak essays (WAW corpus) as compared to good essays (GAW corpus). Both GAW and WAW corpora also show a higher frequency of use in interactive metadiscourse as compared to interactional metadiscourse category. More forms of metadiscourse were found in good essays (GAW corpus) as compared to weak essays (WAW corpus). Thus, the findings of this study give input to the body of knowledge in metadiscourse.